Pengembangan Disain Model Pembelajaran Mobile Learning Berbasis Aplikasi Lectora Inspire sebagai Mindtools pada Proses Pembelajaran Teknologi Pembelajaran - Purwowidodo, Agus (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2018)
Mobile-learning model is an alternative that allows to improve the quality of learning outcomes in FTIK IAIN Tulungagung. This study is aimed to: (1) apply mobile-learning for supporting the conventional learning process of FTIK IAIN Tulungagung; (2) optimalize the quality of learning by implementing mobile learning model in the FTIK IAIN Tulungagung; (3) increase the learning process of the students of FTIK IAIN Tulungagung. The purpose of this research is be able to increase students own potential in the learning process through mobile learning. This research is an action research approach, by designing a system of information technology-based learning via the web portal mobile-learning, which applied on FTIK IAIN Tulungagung, with a sample of 40 students. Based on the research, the results on t-test for Equality of Means show that the value of t learning method with mobile learning is equal to 135,761 (equal variances assummed) with sig (2-tailed) of 0.000. While the t value of conventional method equal to 86,808 (equal variances assummed) with sig (2-tailed) equal to 0,000. The conclusion is